A Comparison of Serum Thyroxine [T4(D)], RT3U Ratio and T4-RT3 Index with Radioiodine Uptake in the TSH Stimulation Test - Höschl, R.; Gimlette, T. M. D. (Nuklearmedizin - NuclearMedicine, 1972)
A total of 236 TSH stimulation tests were performed using 10 units of TSH intramuscularly. 4 hour uptake of 132I, serum thyroxine [T4(D)], T3 binding coefficient [RT3U ratio] and free thyroxine index [T4-RT3 index] were estimated before and 18 hours after TSH.In 88 tests classified by radioiodine uptake change as positive serum thyroxine increased significantly in only 63.7%, T4-RT3 index in 61.5%.Out of 108 tests classified as negative by radioiodine uptake, serum thyroxine increased significantly in 14.8% and T4-RT3 index in 13.0%.The RT3U ratio procedure used was the least reliable parameter in testing thyroid response to TSH stimulation, T4RT3 index was no better than T4(D) alone.The change in serum thyroxine levels in response to TSH stimulation is in our opinion unreliable for the evaluation of TSH tests, and correlates poorly with changes in radioiodine uptake (r = 0.37), for reasons which are discussed.